In silico design of a multi-epitope vaccine against Mycobacterium avium subspecies paratuberculosis - Guo, Weiqi; Wang, Xinyu; Hu, Jiangang; Zhang, Beibei; Zhao, Luru; Zhang, Guangdong; Qi, Jingjing; Wei, Zuzhang; Bao, Yanqing; Tian, Mingxing; Wang, Shaohui (Frontiers in Immunology, 2025)
The widespread chronic enteritis known as Paratuberculosis (PTB) or Johne's disease (JD) is caused by Mycobacterium avium subspecies paratuberculosis (MAP), posing a significant threat to global public health. Given the challenges associated with PTB or JD, the development and application of vaccines are potentially important for disease control. The aim of this study was to design a multi-epitope vaccine against MAP. A total of 198 MAP genomes were analyzed using pan-genome and reverse vaccinology approaches. B-cell and T-cell epitope analysis was performed on the selected promising cross-protective antigens followed by selection of epitopes with high antigenicity, no allergenicity, and no toxicity for the design of the vaccine. The designed vaccine was evaluated through molecular dynamics simulations, molecular docking, and immunological simulations. The results revealed the identification of five promising cross-protective antigens. In total, 10 B-cell epitopes, 10 HTL epitopes, and 9 CTL epitopes were selected for the design of the vaccine. Both the vaccine candidate and the vaccine-TLR4 complex demonstrated considerable stability in molecular dynamics simulations. Molecular docking studies confirmed that the vaccine candidate successfully interacted with TLR4. Immunological simulations showed an increase in both B-cell and T-cell populations after vaccination. Additionally, the vaccine candidate exhibited a codon adaptability index of 1.0 and a GC content of 53.64%, indicating strong potential for successful expression in Escherichia coli. This research developed a multi-epitope vaccine targeting MAP through pan-genomes and reverse vaccinology methods, offering innovative strategies for creating effective vaccines against MAP.